2016
DOI: 10.4088/jcp.15m10276
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends in Lifetime Incidence Rates of First-Time Diagnosed Bipolar and Depressive Disorders Across 16 Years in Danish Psychiatric Hospitals

Abstract: Objective: There is conflicting evidence as to whether or not the incidences of affective disorders are on the rise. The aim of the present study was to identify time trends across 16 years in the incidences of affective disorders in a nationwide sample. Methods: Using the Danish Psychiatric Central Research Registry, age-and sexadjusted incidence rates of diagnosed affective disorders in Danish psychiatric hospitals using ICD-10 classification were calculated per 100,000 person-years for the population aged 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
6
9
4
2
Order By: Relevance
“…Only a weak increase was observed in boys. This is in line with previous studies that have separately studied either diagnosed or self‐reported depression or prescription of ADs .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Only a weak increase was observed in boys. This is in line with previous studies that have separately studied either diagnosed or self‐reported depression or prescription of ADs .…”
Section: Discussionsupporting
confidence: 91%
“…The incidence rate leveled out from 2013 and onwards. Increase in occurrence of depressive disorders among adolescents has also been reported in several other studies from Nordic countries .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In a large UK study, based on primary care diagnoses of depression, the incidence per 1000 personyears among subjects aged 3-18 years were 2.2, 3.0 and 2.0 in 1995, 2002 and 2005, respectively [9]. There have been two register-based time-trend studies on the incidence or cumulative incidence of diagnosed depression in childhood and adolescence in the Nordic countries, one in Denmark and one in Finland [10,11]. The Finnish register-based study focused on birth cohorts born in 1987 and 1997 and it reported that the cumulative incidence of diagnosed unipolar depression and unspecified affective disorders increased during adolescence [11].…”
Section: Introductionmentioning
confidence: 99%